Leadership Influence, Performance Benefits On Employee Performance : Study Of Central Java Regional Police Headquarters Service Employees - Daryadi Daryadi; Gita Sugiyarti (Universitas Kristen Indonesia Toraja, 2022)
This study aims to analyze the influence of the leadership , performance benefits and on employee performance ( Study of employees of the Central Police Regional Services headquarters). Data were obtained through questionnaires and interviews. The results are expected to provide useful information to both leaders and employees.The data obtained were analyzed using descriptive analysis and quantitative statistical analysis. Quantitative analysis using multiple regression analysis to determine the effect of independent variables on the dependent variable , but before the test done first tested the validity and reliability testing and test requirements.Regression analysis showed that the leadership, performance benefits, jointly affect the performance of employees performance part of the Central Police Regional Services headquarters